Dietary zinc deficiency predisposes mice to the development of preneoplastic lesions in chemically-induced hepatocarcinogenesis - Romualdo, Guilherme Ribeiro [UNESP]; Goto, Renata Leme [UNESP]; Henrique Fernandes, Ana Angélica [UNESP]; Cogliati, Bruno; Barbisan, Luis Fernando [UNESP] (Elsevier, 2016)
Although there is a concomitance of zinc deficiency and high incidence/mortality for hepatocellular carcinoma in certain human populations, there are no experimental studies investigating the modifying effects of zinc on hepatocarcinogenesis. Thus, we evaluated whether dietary zinc deficiency or supplementation alter the development of hepatocellular preneoplastic lesions (PNL). Therefore, neonatal male Balb/C mice were submitted to a diethylnitrosamine/2-acetylaminefluorene-induced hepatocarcinogenesis model. Moreover, mice were fed adequate (35 mg/kg diet), deficient (3 mg/kg) or supplemented (180 mg/kg) zinc diets. Mice were euthanized at 12 (early time-point) or 24 weeks (late time-point) after introducing the diets. At the early time-point, zinc deficiency decreased Nrf2 protein expression and GSH levels while increased p65 and p53 protein expression and the number of PNL/area. At the late time-point, zinc deficiency also decreased GSH levels while increased liver genotoxicity, cell proliferation into PNL and PNL size. In contrast, zinc supplementation increased antioxidant defense at both time-points but not altered PNL development. Our findings are the first to suggest that zinc deficiency predisposes mice to the PNL development in chemically-induced hepatocarcinogenesis. The decrease of Nrf2/GSH pathway and increase of liver genotoxicity, as well as the increase of p65/cell proliferation, are potential mechanisms to this zinc deficiency-mediated effect.
Keywords: Antioxidant defense; Diethylnitrosamine; Mouse hepatocarcinogenesis; Preneoplasia; Zinc deficiency; Zinc supplementation